Development of solar cells for IoT applications - Kwek, Zoe Jia Bao (Nanyang Technological University, 2020)
With the Internet of Things (IoT) rapidly expanding and gaining attention, it is expected that billions of objects will be connected to it in the future. Deployment of the wireless sensor nodes (WSN) is required with the development IoT. With IoTWSN essentially having to be energy autonomous, photovoltaic (PV) cells are often used to harvest ambient light energy to power the IoT-WSN. This dismisses the need for battery replacement, allowing the IoT-WSN to be left in a “Deploy and Forget” mode. Recent trending in the miniaturization of IoT-WSN, has led to more research needing to be done to find an alternative way to provide the IoT-WSN with sufficient energy while having footprint sizes reduced. With lesser area available for the solar cell to harvest sufficient energy for the IoT-WSN, one of the possible solutions to it is to use PV-Tower solar cell to harvest light energy. In this report, studies will be done on the IoT and the basic theories of the PV solar cells. An energy autonomous IoT circuit board device was developed and built by integrating the hardware components of the IoT circuit board, the solar cells and the communication module together. The IoT circuit board demonstrated how the solar cell was able to harvest light energy to charge the battery cell, enabling the IoT device to function regularly and allowing wireless transmission of data readings to be uploaded onto a cloud storage (ThingSpeak). Experiments and data collection were done using a conventional planar solar cell and a PV-Tower solar cell. The results gathered proved that it is possible to build an energy autonomous and self-sustaining IoT system which uses solar cell to harvest energy, where it could be left in a “Deploy and Forget” mode. In addition, comparison of energy harvested using the planar solar cell and the PV-Tower solar cell data collection results shows that the PV-Tower solar cell is significantly more efficient and effective in harvesting more solar energy per footprint as compared to the planar solar cell, allowing it to possibly address the footprint size constraints challenges posed by miniaturization of the IoT-WSN.